Comparison between intermittent and continuous leukapheresis protocols for autologous hematopoietic stem cell collections in children. Issue 6 (19th August 2019) - Ali, Salah; Chiang, Kuang‐Yueh; Even‐Or, Ehud; Di Mola, Maria; Schechter, Tal; Ali, Muhammad; McDougall, Elizabeth; Svajger, Gordana; Licht, Christoph; Krueger, Joerg
Abstract: Background: Peripheral hematopoietic stem cell (HSC) collections are needed for autologous hematopoietic stem cell transplantation (HSCT). Since 2015, our institution has utilized a secondary chamber mononuclear cell (MNC) protocol on the Spectra Optia apheresis system. Recently, a new continuous mononuclear collection protocol (CMNC) was developed for the same device. As there is limited data available regarding the use of the CMNC protocol in children, we compared collection efficiency (CE2), side effects, and clinical feasibility between the two protocols in patients <18 years old. Study Design and Methods: We prospectively collected clinical, laboratory, and technical collection data from HSC collection procedures performed with the Spectra Optia apheresis system utilizing the CMNC protocol. Data were compared to retrospectively collected data utilizing the MNC protocol. Data collection included donor demographics, precollection peripheral CD34+ cell counts, total CD34+ cells collected, collection efficiency, side effects, and collection product characteristics. Results: A total of 96 HSC collection procedures were performed on 79 pediatric patients utilizing either the MNC (61 patients) or CMNC (18 patients) protocol. The collection efficiencies were comparable between MNC and CMNC cohorts (52.9% vs 54.9%, P = 0.711). Platelet loss was significantly lower in the CMNC cohort ( P = 0.002), especially in children weighing <15 kg. Product volumes were higher with CMNC. No significant collection‐related side effects were noted with either protocol. Conclusions: MNC and CMNC protocols have comparable collection efficiencies and are both feasible and safe for the use in children. Centers may choose between the methods depending on clinical needs.